AVID Participation in High School and Post-Secondary Success: An Evaluation and Cost Analysis. Issue 4 (1st October 2020) - Todhunter-Reid, Abigail; Burke, Amanda; Houchens, Paul; Howard, Mark
Abstract: The purpose of this study is to evaluate the Advancement Via Individual Determination (AVID) program and to derive estimates of program costs. We used the Coarsened Exact Matching approach to match AVID students with non-AVID students on 40 baseline characteristics. After matching, we estimated group differences in high-school graduation and college enrollment. We used the ingredients method to estimate program costs and calculated cost-effectiveness ratios by the duration of participation. Findings indicate that students who complete at least one AVID elective have higher high school graduation and college enrollment rates than comparable non-AVID students. We discuss how AVID compares to other college outreach programs in terms of costs and effects.